2021
DOI: 10.1007/s12550-021-00427-x
|View full text |Cite
|
Sign up to set email alerts
|

Mycotoxins in wheat cultivated in the Netherlands: results from eight years of field surveys

Abstract: In the period 2009–2018, an annual field survey with commercial arable farms in the Netherlands was held, to collect data on agronomics of wheat fields as well as mycotoxin concentrations of the specific wheat field at harvest. In total, 293 full farm field records over 8 years were obtained. This study aimed to investigate (i) the occurrence of deoxynivalenol (DON) and other mycotoxins, as well as correlations between these mycotoxins, and (ii) the relationships between agronomics and the DON concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Investigating 470 bread wheat and 260 durum wheat samples from the French harvests of 2012, 2013, and 2014, and using a quantification by LC-MS/MS, Orlando et al [ 37 ] found an occurrence of ENNs ranging from 53% (2014) to 91% (2012), and mean values ranged from 47 to 142 µg Kg −1 for bread wheat and from 55 to 596 µg Kg −1 for durum wheat. In a long-term field survey using HPLC-QqQ-MS/MS in The Netherlands, ENA1, ENB, and ENB1 were detected in 14.2%, 46.6%, and 26.2% of the analyzed samples, respectively [ 38 ]. In Algeria, 21 out of 30 (70%) wheat samples were contaminated with ENB1 at concentrations from 19 to 4569 µg Kg −1 , and seven samples were contaminated with ENA at concentrations ranging from 8 to 88 µg Kg −1 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Investigating 470 bread wheat and 260 durum wheat samples from the French harvests of 2012, 2013, and 2014, and using a quantification by LC-MS/MS, Orlando et al [ 37 ] found an occurrence of ENNs ranging from 53% (2014) to 91% (2012), and mean values ranged from 47 to 142 µg Kg −1 for bread wheat and from 55 to 596 µg Kg −1 for durum wheat. In a long-term field survey using HPLC-QqQ-MS/MS in The Netherlands, ENA1, ENB, and ENB1 were detected in 14.2%, 46.6%, and 26.2% of the analyzed samples, respectively [ 38 ]. In Algeria, 21 out of 30 (70%) wheat samples were contaminated with ENB1 at concentrations from 19 to 4569 µg Kg −1 , and seven samples were contaminated with ENA at concentrations ranging from 8 to 88 µg Kg −1 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most extreme value of DON so far reported for wheat/wheat bran was 49000 µg/kg found in Central Europe, with an average contamination of 848 µg/kg [18]. Furthermore, DON characterized as the most frequent mycotoxin in cultivated wheat in The Netherlands, which occurred on average in 54% of the samples with a mean DON contamination of 228 µg/kg [73]. These data come from 8 years of field surveys and revealed that DON contamination in wheat was mainly affected by year and region.…”
Section: Mycotoxins In Wheatmentioning
confidence: 97%
“…Mycotoxin co-occurrence in wheat has been reported in previously published surveys [68][69][70][71] although the figures cannot be directly compared since only a few toxins were analysed, and incidence of co-occurrence is presented only for either animal feed samples [18], or for all matrixes analysed [72]. Finally, data from 8 years of field surveys revealed a co-occurrence of DON and ZEN, and between DON/ZEN and their modified forms in cultivated wheat in the Netherlands [73].…”
Section: Mycotoxins In Wheatmentioning
confidence: 99%
“…Burgess, P.E. Nelson and Toussoun [17,[69][70][71][72]. Types C and D share the presence of a carbonyl group attached to C-8 of the sesquiterpenoid backbone of trichothecenes.…”
Section: Trichothecenes: Biosynthesis and Regulationmentioning
confidence: 99%